Mindfulness interventions. [article]. - Creswell, J. David
Mindfulness interventions aim to foster greater attention to and awareness of present moment experience. There has been a dramatic increase in randomized controlled trials (RCTs) of mindfulness interventions over the past two decades. This article evaluates the growing evidence of mindfulness intervention RCTs by reviewing and discussing (a) the effects of mindfulness interventions on health, cognitive, affective, and interpersonal outcomes; (b) evidence-based applications of mindfulness interventions to new settings and populations (e.g., the workplace, military, schools); (c) psychological and neurobiological mechanisms of mindfulness interventions; (d) mindfulness intervention dosing considerations; and (e) potential risks of mindfulness interventions. Methodologically rigorous RCTs have demonstrated that mindfulness interventions improve outcomes in multiple domains (e.g., chronic pain, depression relapse, addiction). Discussion focuses on opportunities and challenges for mindfulness intervention research and on community applications. -- (from the author)
Keywords: Mindfulness; Meditation; Review; Randomized controlled trial; Health